INNOVATIONS IN MSME DEVELOPMENT OF SMALL INDUSTRIAL PRODUCTS CERAMIC IN BANDAR DUA PIDIE JAYA REGENCY - Ismayli; Fakhrurrazi; Zulfikar (stiatabalong.ac.id, 2023)
ABSTRACT The purpose of this study was to analyze the innovation of MSME development of ceramic small industrial products in Bandar Dua District, Pidie Jaya Regency. The population in this study were all small ceramic industries in Bandar Dua District, Pidie Jaya Regency, which consisted of 3 ceramic businesses, namely Various Work Enterprises, Cheap Raya Enterprises and Makmur Jaya Enterprises, which were studied with a workforce of 42 people. Data was collected using a questionnaire, data analysis uses a multiple linear regression model, with the independent variables of model innovation (X1) and shape/size innovation (X2), as well as the dependent variable of the ceramics industry (Y), with the following formula. The research results show that the relationship between the independent variables and the dependent variable is 69,7%. Meanwhile, to see the coefficient of Termination is 0.486 or (48.6%). This means that 46.6% has an influence between the model development innovation variable and size/shape development innovation on the UMKM Development variable, while the remaining (51.4%) is influenced by other variables not discussed in this study